Japanese Philosophy as the Result of History of the National Spiritual Tradition - Elena Lvovna, Skvortsova (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2024)
This article explores the essence of Japanese philosophy, which has evolved through the convergence of various intellectual traditions, including Shintoism, Buddhism, Confucianism, and Taoism. These spiritual foundations have deeply influenced Japanese self-perceptions, societal relations, and governance structures. Employing a dialectical method combined with the principle of complementarity, this study examined the development of Japanese philosophy, particularly during the Meiji (1868-1912) and Taisho (1912-1925) periods, highlighting the integration of Western philosophical ideas. Key contributions from thinkers such as Nishida Kitaro, who sought to merge Western concepts with Eastern traditions, are discussed. This study also emphasizes the importance of traditional Japanese arts and bodily synthesis in shaping philosophical thought. The unique ability of Japanese philosophy to adapt and transform diverse intellectual traditions is a central theme, illustrating its capacity to generate new meanings and approaches. The continuous influence of medieval categories and modern developments showcases a holistic approach that integrates both old and new perspectives. This adaptability is crucial in addressing contemporary issues such as the interaction between information culture and historical spiritual traditions. The study concludes that the flexibility and integrative nature of Japanese philosophy, exemplified by figures such as Nishida Kitaro and Imamichi Tomonobu, remain vital for contemporary philosophical discourse.